(untitled) (Mugda Medical College Journal, 2024)
Background: Type 2 diabetes in children and adolescents has increased in frequency around the world over the past two decades. The worldwide epidemic of childhood obesity has been accompanied by an increase in the incidence of type 2 diabetes in children and adolescents. Objective: To observe the determinants of type 2 diabetes mellitus among children and adolescents attending a tertiary specialized hospital in Bangladesh. Methods: This cross-sectional, descriptive study was done on a total of 151 children and adolescents attending the pediatric diabetic outpatient department (OPD) of Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine, and Metabolic Disorders (BIRDEM) Hospital, Dhaka, Bangladesh. The sampling technique was purposive. All patients who came to the hospital between July to December 2017 were included. Data was collected through a structured questionnaire. Results: Among 151 respondents, 98 were in the age group of 10-14 years (64.9%), female to male ratio of 1.22:1. The majority belonged to a high used to lead socio-economic class. Regarding food habits, 55.6% had a history of eating fast food regularly and used to lead a sedentary lifestyle with a lack of exercise. 43.7% of children and adolescents were obese 76.8% had high cholesterol and 84.1% had high triglyceride levels. Most of the children had a positive family history of type 2 diabetes mellitus (74.8%). Conclusion: Our study reflects that determinants like obesity, physical inactivity, eating habits, and family history are important factors in the development of type 2 diabetes mellitus in children and adolescents. Mugda Med Coll J. 2023; 6(2): 51-56